WB5−x: Synthesis, Properties, and Crystal Structure—New Insights into the Long‐Debated Compound. Issue 16 (2nd July 2020) - Kvashnin, Alexander G.; Rybkovskiy, Dmitry V.; Filonenko, Vladimir P.; Bugakov, Vasilii I.; Zibrov, Igor P.; Brazhkin, Vadim V.; Oganov, Artem R.; Osiptsov, Andrey A.; Zakirov, Artem Ya
Abstract: The recent theoretical prediction of a new compound, WB5, has spurred the interest in tungsten borides and their possible implementation in industry. In this research, the experimental synthesis and structural description of a boron‐rich tungsten boride and measurements of its mechanical properties are performed. The ab initio calculations of the structural energies corresponding to different local structures make it possible to formulate the rules determining the likely local motifs in the disordered versions of the WB5 structure, all of which involve boron deficit. The generated disordered WB4.18 and WB4.86 models both perfectly match the experimental data, but the former is the most energetically preferable. The precise crystal structure, elastic constants, hardness, and fracture toughness of this phase are calculated, and these results agree with the experimental findings. Because of the compositional and structural similarity with predicted WB5, this phase is denoted as WB5− x . Previously incorrectly referred to as "WB4, " it is distinct from earlier theoretically suggested WB4, a phase with a different crystal structure that has not yet been synthesized and is predicted to be thermodynamically stable at pressures above 1 GPa. Mild synthesis conditions (enabling a scalable synthesis) and excellent mechanical properties make WB5− x a very promising material for drilling technology. Abstract : New boron‐rich tungsten boride WB5− x is synthesized in an experiment, its precise crystal structure is determined, and mechanical properties are measured. The calculated values of the elastic constants, hardness, and fracture toughness of the new material agree with the experimental findings. A comprehensive theoretical investigation makes it possible to resolve the puzzle of "WB4 " widely discussed over the past 50 years.